PERSEPSI MASYARAKAT TEMPATAN TERHADAP RAINFOREST WORLD MUSIC FESTIVAL 2022 = Local Community Perception of Rainforest World Music Festival 2022 - Nurul Najihah, Masuut; Shaik Azahar, Shaik Hussain (Researchgate, 2023)
The Rainforest World Music Festival organised at the Sarawak Cultural Village is a very celebrated event, and as a world music festival, it has global awareness. Based on the results of the work that has been carried out, this study aims to determine the perception of the influencing factors of the number of visitors, methods of promoting Sarawak culture, and the impact of organising the Rainforest World Music Festival from the perspective of the local community. A survey based on a questionnaire was carried out face-to-face and through Google Form software, and finally, a total of 388 respondents participated. The researcher has analysed the data obtained and made further discussions by performing a crosstabulation analysis on the demographics of the respondents with the questions in the questionnaire. The researcher also put forward some views and suggestions as a benefit to stakeholders related to this study.